Study of the Influence of Native Polymer Sulfur on the Rheological Properties of Rubber Compounds (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Polymer sulfur, obtained from local raw materials, was synthesized in laboratory conditions. The improvement of the physical and mechanical properties of rubber compounds obtained on the basis of natural polymer sulfur has been studied. The physical and mechanical properties of the reference rubber mixture and the sulfur-based polymer rubber mixture were studied.